Diseño y caracterización de nuevas herramientas para el diagnóstico de la tuberculosis bovina - Villafañe, Luciana María (2024)
Bovine tuberculosis is an infectious, contagious, zoonotic, and endemic disease caused by Mycobacterium bovis, which affects cattle. The international reference diagnostic test is the intradermal reaction. The IFN-? test is also employed to improve diagnostic sensitivity. This test detects the in vitro release of IFN-? after stimulation with M. bovis antigens. This research aimed at designing and developing new tools for the differential diagnosis of bovine tuberculosis by identifying new M. bovis antigens and generating anti-bovine IFN-? antibodies. M. bovis proteins were selected using bioinformatics techniques and expressed recombinantly in E. coli and baculovirus to identify new antigens. Subsequently, the proteins were evaluated in IFN-?-release and anti-M. bovis-antibody detection assays. In addition, recombinant bovine IFN-? was produced in E. coli to generate mono and polyclonal antibodies in mice, camelids and birds. PolH-Mb0309, PolH-EsxG, and the BvCk mixture (PolH-ESAT-6/PolH-CFP-10/PolH-Mb3645c) induced differential release of IFN-? in samples from animals sensitized with M. bovis, while His-Mb2002c allowed the detection of anti-M. bovis antibodies. In capture ELISA assays, camelid antibodies were able to identify bovine IFN-? captured. The antigens and antibodies obtained in this study represent progress in the bovine tuberculosis diagnosis optimization.